Reactive hot-melt adhesive composition and bonding method
Patent Information
- Application Number
- JP2023127977
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
AI Technical Summary
【0016】 本発明によれば、初期接着強度が高く、溶融粘度が低い反応性ホットメルト接着剤組成物を提供することができる。
Smart Images

Figure 2025023649000002 
Figure 2025023649000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a reactive hot melt adhesive composition and a bonding method. [Background technology]
[0002] Hot melt adhesives are suitable for improving productivity because they can obtain adhesive strength in a short time. Hot melt adhesives include thermoplastic and reactive types. Of these, reactive types, i.e. reactive hot melt adhesives, undergo chemical reactions such as curing after adhesion. Therefore, reactive hot melt adhesives can provide adhesion with higher adhesive strength and higher heat resistance than thermoplastic types, and are widely used in applications where adhesive reliability is required.
[0003] Many reactive hot melt adhesives contain urethane prepolymers with isocyanate groups (-N=C=O) at the ends. After bonding, reactive hot melt adhesives containing urethane prepolymers develop a certain degree of adhesive strength in a short time as the adhesive itself cools and hardens. The isocyanate groups at the ends of the urethane prepolymers then react with moisture in the air or on the surface of the adherend, resulting in high molecular weight or crosslinking. This increases the adhesive's cohesive strength and heat resistance, and the adhesive joints exhibit high adhesive strength even when heated.
[0004] Examples of reactive hot melt adhesives include those having the following configurations.
[0005] Patent Document 1 describes a reactive hot melt adhesive composition comprising a urethane prepolymer having an isocyanate group at the molecular end, a thermoplastic resin, and a tackifier, in which the melt viscosity of the thermoplastic resin in the application temperature range is lower than the melt viscosity of the tackifier in the same temperature range.
[0006] Patent Document 2 describes a reactive hot melt urethane adhesive composition containing a thermoplastic polymer, a cured urethane-polyalkylene polyol prepolymer, and a tackifier.
[0007] Patent Document 3 describes a reactive hot melt adhesive that includes a urethane polymer having two or more active isocyanate groups in the molecule, a polyethylene having a specific gravity of 0.915 to 0.938, and a specific tackifier.
[0008] Patent Document 4 describes a reactive hot melt adhesive composition that contains a urethane prepolymer (i) having an isocyanate group obtained by reacting a polyester polyol (A), a polyether polyol (B), and an isocyanate (C), and an acrylic polymer (ii), in which the polyester polyol (A) is composed of a crystalline polyester polyol (A-1) and an amorphous polyester polyol (A-2), and both the amorphous polyester polyol (A-2) and the acrylic polymer (ii) have aromatic rings.
[0009] Patent Document 5 describes a moisture-curable reactive hot melt adhesive composition that contains (A) a urethane prepolymer having an isocyanate group and (B) an acrylic polymer, in which the acrylic polymer (B) has a glass transition temperature of 50°C or higher and a weight average molecular weight of 50,000 or higher, and the content of the acrylic polymer is 5 to 25 mass% based on the total amount of the composition. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Japanese Patent Application Publication No. 06-122860 [Patent Document 2] Japanese Patent Application Publication No. 64-054089 [Patent Document 3] Japanese Patent Application Publication No. 52-037936 [Patent Document 4] Patent No. 6662376 [Patent Document 5] JP 2019-172881 A Summary of the Invention [Problem to be solved by the invention]
[0011] Depending on the application, hot melt adhesives may be required to have high initial adhesive strength. However, reactive hot melt adhesives take a long time to cool and solidify and to increase their molecular weight, so their initial adhesive strength to the substrate may be insufficient.
[0012] As described in Patent Documents 1 to 5, the initial adhesive strength can be improved by blending a thermoplastic resin into a reactive hot melt adhesive, but the addition of a thermoplastic resin also tends to increase the melt viscosity of the adhesive. If the melt viscosity of the adhesive becomes high, it becomes unsuitable for cases where application to a fine structure is required.
[0013] Therefore, an object of the present invention is to provide a reactive hot melt adhesive composition having high initial adhesive strength and low melt viscosity. [Means for solving the problem]
[0014] In order to achieve the above object, the present invention has the following configuration.
[0015] [1] A reactive hot melt adhesive composition comprising: a urethane prepolymer (A) consisting of a compound having a structure derived from a polyol and an isocyanate group at at least one end of the structure derived from the polyol; a (meth)acrylic polymer (B) which is a polymer having a structural unit derived from a (meth)acrylic acid ester; and a filler (C), wherein the (meth)acrylic polymer (B) has a glass transition temperature of 65°C or higher and a weight average molecular weight of 100,000 or less. [2] The reactive hot melt adhesive composition according to [1], further comprising a thermoplastic elastomer. [3] The reactive hot melt adhesive composition according to [1] or [2], wherein the filler (C) comprises an inorganic filler. [4] The reactive hot melt adhesive composition according to [1] or [2], wherein the (meth)acrylic polymer (B) has a glass transition temperature of 100° C. or lower. [5] The reactive hot melt adhesive composition according to [1] or [2], wherein the structure derived from the polyol includes at least one of a structure derived from a polyester polyol and a structure derived from a polyether polyol. [6] The reactive hot melt adhesive composition according to [1] or [2], wherein the urethane prepolymer (A) comprises a polyester polyol having an isocyanate group at least at either end and a polyether polyol having an isocyanate group at least at either end. [7] The reactive hot melt adhesive composition according to [1] or [2], wherein the content of the urethane prepolymer (A) is 45% by mass or more and 95% by mass or less, the content of the (meth)acrylic polymer (B) is 3.0% by mass or more and 25% by mass or less, and the content of the filler (C) is 1.0% by mass or more and 10% by mass or less. [8] The reactive hot melt adhesive composition according to [2], wherein the content of the urethane prepolymer (A) is 45% by mass or more and 90% by mass or less, the content of the (meth)acrylic polymer (B) is 3.0% by mass or more and 25% by mass or less, the content of the filler (C) is 1.0% by mass or more and 10% by mass or less, and the content of the thermoplastic elastomer is 3.0% by mass or more and 20% by mass or less. [9] A reactive hot melt adhesive composition according to [1] or [2], having an initial adhesive strength, which is the adhesive strength 1 minute after bonding, of 0.17 MPa or more and a melt viscosity at 120°C of 9.0 Pa s or less. Effect of the Invention
[0016] According to the present invention, it is possible to provide a reactive hot melt adhesive composition having high initial adhesive strength and low melt viscosity. [Brief description of the drawings]
[0017] [Figure 1]FIG. 2 is a plan view showing a method for measuring the initial adhesive strength of an adhesive composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, the embodiments of the present invention will be described in detail, however, the present invention is not limited to the following embodiments.
[0019] In the following description, "(meth)acrylic" is a general term for acrylic and methacrylic, and "(meth)acrylate" is a general term for acrylate and methacrylate.
[0020] The term "reactive hot melt adhesive composition" refers to a composition that, upon reacting with moisture (humidity) in the air or on the surface of an adherend, undergoes a high molecular weight and exhibits improved properties such as adhesiveness.
[0021] The glass transition temperature is the peak top temperature of a DDSC chart obtained as the temperature derivative of DSC when a dry sample is subjected to DSC measurement under the following conditions using a differential scanning calorimeter (DSC-60A-Puls, manufactured by Shimadzu Corporation). Sample size: 10-15mg Measurement temperature: 25~100℃ Heating rate: 10℃ / min Atmosphere gas: Nitrogen Gas flow rate: 50mL / min Cell: Al
[0022] A certain structure X (e.g., a structure derived from a polyol) contained in the urethane prepolymer (A) described below means a structure X possessed by a compound contained in the urethane prepolymer (A). In other words, the content of a certain structure X contained in the urethane prepolymer (A) is the total amount of structure X possessed by a compound contained in the urethane prepolymer (A). When structure X is a structure derived from a polyol, it is considered to include oxygen atoms in the urethane bond at both ends of the structure and hydrogen atoms bonded to nitrogen atoms forming the urethane bond.
[0023] The content of a certain structure X in the urethane prepolymer (A) is the mass ratio of the structure X contained in these compounds to the total mass of the compounds contained in the urethane prepolymer (A). Note that in this calculation, the structure derived from the polyol is considered to include the oxygen atoms in the urethane bonds at both ends of the structure and the hydrogen atoms bonded to the nitrogen atoms forming the urethane bonds.
[0024] [Reactive hot melt adhesive composition] The reactive hot melt adhesive composition according to the present embodiment (hereinafter, sometimes referred to as "adhesive composition") contains a urethane prepolymer (A), a (meth)acrylic polymer (B), and a filler (C). The adhesive composition according to the present embodiment may contain other components. The other components preferably contain a thermoplastic elastomer (TPE). The components contained in the adhesive composition according to the present embodiment, the components preferably contained therein, and other components that may be contained therein will be described below.
[0025] [Urethane prepolymer (A)] The urethane prepolymer (A) is composed of a structure derived from a polyol and a compound having an isocyanate group at at least one end of the structure derived from a polyol. The adhesive composition according to the present embodiment can exhibit excellent adhesiveness after moisture curing by including the urethane prepolymer (A). The urethane prepolymer (A) may include a compound having a structure derived from a plurality of polyols with different structures (e.g., a structure derived from a polyisocyanate) sandwiched therebetween. The urethane prepolymer (A) may include a compound having a structure having a sequence such as isocyanate group-polyol-polyisocyanate-polyol-polyisocyanate-polyol-polyisocyanate-polyol-isocyanate-polyol-isocyanate group.
[0026] The urethane prepolymer (A) preferably contains a compound having isocyanate groups at multiple ends, more preferably contains a compound having isocyanate groups at two ends, and even more preferably contains a compound of a linear molecule having isocyanate groups at both ends. The urethane prepolymer (A) more preferably contains 90% by mass or more of a compound having isocyanate groups at two ends, and even more preferably contains 95% by mass or more. The urethane prepolymer (A) may be composed of a compound having isocyanate groups at two ends.
[0027] Examples of polyol compounds from which the structure of the compound contained in the urethane prepolymer (A) is derived include polyester polyols, polyether polyols, acrylic polyols, polyolefin polyols, polybutadiene polyols, polyisoprene polyols, rosin-modified polyols, polyethylene butylene polyols, polycarbonate polyols, polycaprolactone polyols, etc. Of these compounds, the polyol compound is preferably a diol compound.
[0028] The content of the structure derived from the polyol in the urethane prepolymer (A) is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more.
[0029] The content of the structure derived from the polyol in the urethane prepolymer (A) is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less.
[0030] The structure derived from the polyol contained in the urethane prepolymer (A) preferably includes at least one of a structure derived from a polyester polyol and a structure derived from a polyether polyol, and more preferably includes both a polyester polyol and a polyether polyol.
[0031] The urethane prepolymer (A) may be configured to include a compound having one of a structure derived from a polyester polyol and a structure derived from a polyether polyol. The urethane prepolymer (A) may be configured to include a compound having a structure derived from a polyester polyol without a structure derived from a polyether polyol, and a compound having a structure derived from a polyether polyol without a structure derived from a polyester polyol. In addition to these compounds, the urethane prepolymer (A) may be configured to include a compound having both a structure derived from a polyester polyol and a structure derived from a polyether polyol.
[0032] The urethane prepolymer (A) preferably contains a polyester polyol having an isocyanate group at least at either end, and a polyether polyol having an isocyanate group at least at either end.
[0033] In the urethane prepolymer (A), when the structure derived from a polyol includes both a structure derived from a polyester polyol and a structure derived from a polyether polyol, the mass ratio of the structure derived from the polyester polyol to the structure derived from the polyether polyol (polyester polyol / polyether polyol) is preferably 0.20 or more, more preferably 0.30 or more, and even more preferably 0.40 or more.
[0034] In the urethane polymer (A), when the structure derived from a polyol includes both a structure derived from a polyester polyol and a structure derived from a polyether polyol, the mass ratio of the structure derived from the polyester polyol to the structure derived from the polyether polyol (polyester polyol / polyether polyol) is preferably 1.0 or less, more preferably 0.80 or less, and even more preferably 0.60 or less.
[0035] The polyisocyanate compound from which the structure of the compound contained in the urethane prepolymer (A) is derived preferably contains a diisocyanate compound, such as diphenylmethane diisocyanate, dimethyldiphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, tolylene diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, p-phenylene diisocyanate, isophorone diisocyanate, etc.
[0036] The content of the structure derived from polyisocyanate in the urethane prepolymer (A) is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more.
[0037] The content of the structure derived from polyisocyanate in the urethane prepolymer (A) is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less.
[0038] In the urethane prepolymer (A), the proportion of the structure derived from a diisocyanate compound in the structure derived from a polyisocyanate compound is preferably 90% by mass or more, more preferably 95% by mass or more. In the urethane prepolymer (A), the structure derived from a polyisocyanate compound may be composed of a structure derived from a diisocyanate compound.
[0039] The polyisocyanate compound preferably contains an aromatic diisocyanate, because this improves the mechanical properties such as strength and heat resistance of the adhesive layer obtained from the adhesive composition.
[0040] If the ratio of the isocyanate group (NCO) equivalent of the polyisocyanate compound used in the synthesis of the urethane prepolymer (A) to the hydroxyl group (OH) equivalent of the polyol compound is defined as NCO / OH, it is preferable that NCO / OH is in the following range.
[0041] In the synthesis of the urethane prepolymer (A), the NCO / OH ratio is preferably 1.1 or more, more preferably 1.5 or more, and even more preferably 1.8 or more. This is because a larger amount of polyurethane having an isocyanate group at its terminal (i.e., the urethane prepolymer (A)) can be obtained. In addition, the viscosity of the obtained urethane prepolymer (A) falls within an appropriate range, which makes it possible to improve workability.
[0042] In the synthesis of the urethane prepolymer (A), the NCO / OH ratio is preferably 3.0 or less, more preferably 2.5 or less, and even more preferably 2.2 or less, because this makes it possible to suppress foaming during the moisture curing reaction and improve the adhesiveness.
[0043] [(Meth)acrylic polymer (B)] The (meth)acrylic polymer (B) is a polymer having a structural unit derived from a (meth)acrylic acid ester. Here, the structural unit derived from a (meth)acrylic acid ester is a structural unit represented by -CH2CH(COOR)- or -CH2C(CH3)(COOR)-, where R is any organic group. The reactive hot melt adhesive can improve the initial adhesive strength by including the (meth)acrylic polymer (B). The (meth)acrylic polymer (B) preferably does not have a crosslinked structure. This is to ensure that the adhesive composition is sufficiently melted. Note that, if sufficient applicability is maintained when the adhesive composition is melted, the (meth)acrylic polymer (B) may contain a component having a crosslinked structure.
[0044] The (meth)acrylic polymer (B) may be a copolymer of a (meth)acrylic acid ester and another compound. The ratio of structural units derived from a (meth)acrylic acid ester in the (meth)acrylic polymer (B) is preferably 60 mol % or more, more preferably 80 mol % or more, even more preferably 90 mol % or more, and most preferably 100 mol %.
[0045] Examples of (meth)acrylic acid esters include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, neopentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, cetyl (meth)acrylate, and lauryl (meth)acrylate; (meth)acrylic acid esters having fluorine atoms such as 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, and 2-(perfluorooctyl)ethyl (meth)acrylate; isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, and the like. Examples of the (meth)acrylic acid esters include (meth)acrylic acid esters having an alicyclic structure such as cyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, etc.; (meth)acrylic acid esters having an ether bond such as polyethylene glycol mono(meth)acrylate, methoxyethyl (meth)acrylate, methoxybutyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, etc.; (meth)acrylic acid esters having an aromatic ring such as benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, etc.; (meth)acrylic acid esters having a functional group such as 2-ethyl-2-methyl-[1,3]-dioxolan-4-yl-methyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, glycidyl (meth)acrylate, cyano (meth)acrylate, etc. The (meth)acrylic polymer may contain only one type of structural unit derived from these (meth)acrylic acid esters, or may contain two or more types.
[0046] The (meth)acrylic polymer (B) may contain, in addition to the (meth)acrylic acid ester, a structural unit derived from a compound having an ethylenically unsaturated bond such as styrene, (meth)acrylonitrile, etc. The (meth)acrylic polymer (B) may contain only one type of structural unit derived from a compound other than the (meth)acrylic acid ester, or may contain two or more types of structural units.
[0047] The method for producing the (meth)acrylic polymer (B) is not particularly limited, but examples thereof include solution polymerization, suspension polymerization, and bulk polymerization.
[0048] The glass transition temperature Tg of the (meth)acrylic polymer (B) is 65° C. or higher, preferably 75° C. or higher, and more preferably 85° C. or higher, because this improves the initial adhesive strength of the reactive hot melt adhesive.
[0049] The glass transition temperature Tg of the (meth)acrylic polymer (B) is preferably 100° C. or lower, more preferably 97° C. or lower, and even more preferably 94° C. or lower, in order to sufficiently melt the reactive hot melt adhesive.
[0050] In addition, when the (meth)acrylic polymer (B) is a block copolymer or the like, and the molecular chain contains at least a portion of segments formed from the same structural units, these segments and other portions all have a glass transition temperature within the required or preferred range.
[0051] Here, the weight average molecular weight Mw of the (meth)acrylic polymer (B) is a polystyrene equivalent value measured by GPC (gel permeation chromatography) and is a value measured according to the description of the examples described later. The weight average molecular weight Mw of the (meth)acrylic polymer (B) is preferably 10,000 or more, more preferably 20,000 or more, and even more preferably 25,000 or more. This is to improve the initial adhesive strength of the adhesive composition.
[0052] The weight average molecular weight Mw of the (meth)acrylic polymer (B) is 100,000 or less, preferably 80,000 or less, and more preferably 70,000 or less, in order to suppress an increase in the melt viscosity of the adhesive composition.
[0053] [Filler (C)] The filler (C) preferably contains an inorganic filler, more preferably contains at least one of silicate and silicon oxide. Examples of silicate include talc and mica, examples of silicon oxide include silica gel, and other inorganic fillers include calcium carbonate. It is particularly preferable that the filler (C) contains at least one of talc and silica gel.
[0054] The proportion of the inorganic filler in the filler (C) is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more. The proportion of the inorganic filler in the filler (C) may be 100% by mass.
[0055] [Thermoplastic elastomer] Thermoplastic elastomers have a glass transition temperature Tg of 25° C. or lower, but for example, in a configuration having a soft segment and a hard segment described below, the glass transition temperature may appear at two or more points, one below 25° C. and one above 25° C. Examples of thermoplastic elastomers include ethylene-based copolymers, propylene-based copolymers, styrene-based copolymers, vinyl chloride-based copolymers, acrylic copolymers, and styrene-conjugated diene block copolymers.
[0056] The thermoplastic elastomer is preferably a ternary block copolymer having a hard segment-soft segment-hard segment structure. An example of an acrylic copolymer having such a structure is a ternary block copolymer (PMMA-PnBA-PMMA) of (polymethyl methacrylate)-(polyn-butyl acrylate)-(polymethyl methacrylate). An example of a styrene-conjugated diene block copolymer having such a structure is a ternary block copolymer of polystyrene-polybutadiene-polystyrene.
[0057] [Other ingredients] To the adhesive composition according to the present embodiment, tackifying resins such as rosin resin, rosin ester resin, hydrogenated rosin ester resin, terpene resin, terpene phenol resin, hydrogenated terpene resin, petroleum resin, hydrogenated petroleum resin, coumarone resin, ketone resin, styrene resin, modified styrene resin, xylene resin, and epoxy resin; catalysts such as dibutyltin dilaurate, dibutyltin dioctate, dimethylcyclohexylamine, dimethylbenzylamine, and trioctylamine; pigments, antioxidants, ultraviolet absorbers, surfactants, and flame retardants may be added as necessary.
[0058] [Content of each component in the adhesive composition] The content of the urethane prepolymer (A) in the adhesive composition is preferably 45% by mass or more, more preferably 55% by mass or more, further preferably 65% by mass or more, and particularly preferably 75% by mass or more, in order to improve the adhesive strength of the adhesive composition after reaction.
[0059] The content of the urethane prepolymer (A) in the adhesive composition is preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less, in order to improve the initial adhesive strength of the adhesive composition by the (meth)acrylic polymer (B) and the filler (C).
[0060] When the adhesive composition contains a thermoplastic elastomer, the content of the urethane prepolymer (A) in the adhesive composition is preferably 90 mass % or less, and more preferably 85 mass % or less.
[0061] The content of the (meth)acrylic polymer (B) in the adhesive composition is preferably 3.0% by mass or more, more preferably 5.0% by mass or more, further preferably 7.0% by mass or more, and particularly preferably 8.0% by mass or more, in order to improve the initial adhesive strength of the adhesive composition.
[0062] The content of the (meth)acrylic polymer (B) in the adhesive composition is preferably 25% by mass or less, more preferably 20% by mass or less, further preferably 15% by mass or less, and particularly preferably 10% by mass or less, in order to fully dissolve the (meth)acrylic polymer (B) in the adhesive composition, to further suppress an increase in the viscosity of the adhesive composition, and to further improve the impact strength of the adhesive layer formed by curing the adhesive composition.
[0063] The content of the filler (C) in the adhesive composition is preferably 1.0% by mass or more, more preferably 2.0% by mass or more, and even more preferably 2.5% by mass or more, in order to improve the initial adhesive strength of the adhesive composition.
[0064] The content of the filler (C) in the adhesive composition is preferably 10% by mass or less, more preferably 8.0% by mass or less, further preferably 6.0% by mass or less, and particularly preferably 4.0% by mass or less, in order to further improve the impact strength of the adhesive layer formed by curing the adhesive composition.
[0065] The content of the thermoplastic elastomer in the adhesive composition is preferably 3.0% by mass or more, more preferably 5.0% by mass or more, even more preferably 7.0% by mass or more, and particularly preferably 8.0% by mass or more, in order to further improve the impact strength of the adhesive layer formed by curing the adhesive composition.
[0066] The content of the thermoplastic elastomer in the adhesive composition is preferably 20% by mass or less, more preferably 15% by mass or less, further preferably 10% by mass or less, and particularly preferably 9.0% by mass or less, in order to sufficiently dissolve the thermoplastic elastomer in the adhesive composition and to improve the initial adhesive strength of the adhesive composition.
[0067] [Melt viscosity of adhesive composition] The melt viscosity of the adhesive composition was measured using a BH-HH type small volume rotational viscometer (manufactured by Toki Sangyo Co., Ltd.) with a No. 4 rotor at a rotor rotation speed of 50 min -1 The melt viscosity is a value measured at 120°C. The melt viscosity of the adhesive composition according to this embodiment is preferably 9.0 Pa s or less, more preferably 7.0 Pa s or less, and even more preferably 5.0 Pa s or less. If the melt viscosity at 120°C is low, various coating devices can be used, and stable dischargeability tends to be obtained, particularly when the adhesive composition is coated in a small amount.
[0068] [Initial adhesive strength of adhesive composition] 1 is a plan view showing a method for measuring the initial adhesive strength of an adhesive composition. The initial adhesive strength of an adhesive composition is the adhesive strength one minute after adhesion, and is a value measured by the following method. In the following description, the center of a rectangular (rectangular and square) plate-like member is the intersection of two diagonals when the member is viewed in a plan view (thickness direction).
[0069] In an environment of 23°C temperature and 50% RH relative humidity, the adhesive composition melted at 100°C is applied to a polycarbonate plate 1 of 60 mm length × 80 mm width × 5 mm thickness with a through hole 11 of 17 mm diameter at its center, so as to draw a square with one side being 30 mm long. Here, the center of the polycarbonate plate 1 and the center of the square drawn by the adhesive composition are aligned.
[0070] Next, an acrylic plate 2 measuring 50 mm long x 75 mm wide x 0.2 mm thick is pressure-bonded to the adhesive-coated surface of the polycarbonate plate 1. At this time, the acrylic plate 2 is pressure-bonded so that the direction of the short side of the acrylic plate 2 coincides with the direction of the long side of the polycarbonate plate 1, and the center of the acrylic plate 2 coincides with the center of the polycarbonate plate 1. At this time, a 0.10 mm thick aluminum plate is sandwiched as a spacer (not shown) between the polycarbonate plate 1 and the acrylic plate 2 on the outside of the square drawn by the adhesive, and a load of 3 kgw is applied to the entire overlapping portion of the polycarbonate plate 1 and the acrylic plate 2 using a weight for 10 seconds, and the weight is then removed.
[0071] In this way, an adhesive layer 3 is formed between the polycarbonate plate 1 and the acrylic plate 2, forming a 30 mm square with a width of 1 mm and a thickness of 0.1 mm. One minute after removing the weight, the indentation adhesive strength is measured using an indentation tester (manufactured by Shimadzu Corporation). For the measurement, the vicinity of both vertical sides (short sides) 12 and 13 of the polycarbonate plate 1 is chucked, and the center of the acrylic plate 2 is pressed at a pressing speed of 10 mm / min using a cylindrical presser 4 with a diameter of 10 mm. The load is measured at the point when the load stops increasing, and this load value is taken as the initial adhesive strength of the adhesive composition.
[0072] The initial adhesive strength of the adhesive composition according to this embodiment is preferably 0.17 MPa or more, more preferably 0.22 MPa or more, and even more preferably 0.25 MPa or more, because this improves the productivity of the bonding process using the adhesive composition.
[0073] [Adhesion method using adhesive composition] Various members can be bonded using the adhesive composition according to the present embodiment. The bonding method according to the present embodiment includes, for example, a coating step of coating a molten adhesive composition on a first member, a mounting step of mounting a second member on the surface of the first member on which the adhesive composition is applied, and a reaction step of reacting the applied adhesive composition in air containing moisture, but is not limited to these steps. For example, the adhesive composition may be applied to the bonding surfaces of both the first member and the second member.
[0074] The method of applying the adhesive composition is not particularly limited, but for example, the adhesive composition can be applied while being discharged from an air dispenser. In this case, from the viewpoint of workability, it is preferable that the adhesive composition be heated to 80 to 130°C before being discharged.
[0075] The relative humidity of the air in the step of reacting the adhesive composition is preferably 20% RH or more, more preferably 30% RH or more, and even more preferably 40% RH or more, in order to improve the reaction speed of the adhesive composition and achieve strong adhesion in a shorter time.
[0076] Examples of materials that can be bonded with the adhesive composition of this embodiment include metals and alloys such as SUS and aluminum, polymeric materials such as polycarbonate, polyamide, and polybutylene terephthalate, and inorganic materials such as glass and metal oxides. EXAMPLES
[0077] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples.
[0078] The raw materials used are as follows: Polyol compound (a): polyester diol (ester of 1,6-hexanediol and adipic acid, number average molecular weight: 5000) Polyol compound (b): polyester diol (ester of ethylene glycol and adipic acid, number average molecular weight: 2000) Polyol compound (c): polytetramethylene glycol (manufactured by Hodogaya Chemical Co., Ltd., product name "PTG2000SN", number average molecular weight: 2000) Polyol compound (d): Polypropylene glycol (manufactured by AGC Corporation, product name "Exenol 1020" ("Exenol" is a registered trademark), number average molecular weight: 1000) Polyisocyanate compound: Diphenylmethane diisocyanate (manufactured by Tosoh Corporation, product name "Millionate MT") (Meth)acrylic polymer (a): (meth)acrylic polymer (manufactured by Mitsubishi Chemical Corporation, product name "BR113", weight average molecular weight: 29,000, glass transition temperature: 91°C) (Meth)acrylic polymer (b): (meth)acrylic polymer (manufactured by Mitsubishi Chemical Corporation, product name "BR106", weight average molecular weight: 52,000, glass transition temperature: 69°C) (Meth)acrylic polymer (c): (meth)acrylic polymer (manufactured by Evonik Degussa, product name "DYNACOLL AC1750", weight average molecular weight: 110,000, glass transition temperature: 71°C) (Meth)acrylic polymer (d): (meth)acrylic polymer (manufactured by Mitsubishi Chemical Corporation, product name "BR117", weight average molecular weight: 140,000, glass transition temperature: 60°C) Filler (a): Talc (manufactured by Asada Flour Milling Co., Ltd., product name "FFR") Filler (b): Silica gel (manufactured by Evonik Degussa, product name "R202") Thermoplastic elastomer: PMMA-PnBA-PMMA block copolymer (manufactured by Kuraray Co., Ltd., product name "LA3320")
[0079] The weight average molecular weight Mw and number average molecular weight Mn of the (meth)acrylic polymers (a) to (d) were measured by gel permeation chromatography (GPC). Specifically, the measurements were performed using a Chromaster MODEL CMORG, CM5456 manufactured by Hitachi High-Tech Corporation under the following conditions, and the values were calculated in terms of standard polystyrene.
[0080] Columns: A130-S, A160-S, A150-S manufactured by Resonac Technoservice Co., Ltd. Column flow rate: 1mL / min Column temperature: 35℃ Mobile phase: THF (tetrahydrofuran) Sample volume: 0.07mL Sample concentration: 1% by mass Dilution solvent: THF (tetrahydrofuran)
[0081] The amount of each component used in each Example and Comparative Example is shown in Table 1. In each Example and Comparative Example, a composition was obtained by carrying out the following operations. The values shown in Table 1 as mass% are the mass ratios of the components used in each Example and Comparative Example to the total amount of the components shown in Table 1.
[0082] [Example 1] 8.9 parts by mass of (meth)acrylic polymer (a), 8.9 parts by mass of thermoplastic elastomer, and 25.0 parts by mass of polyol compound (d) were put into a 1L glass round-bottom flask, and mixed and stirred while raising the internal temperature from room temperature (25°C) to 150°C under a nitrogen gas flow, to dissolve the (meth)acrylic polymer in the liquid components. Further, 10.1 parts by mass of polyol compound (a), 10.1 parts by mass of polyol compound (b), 14.3 parts by mass of polyol compound (c), and 3.0 parts by mass of filler (a) were put in, and dehydration was performed at 95°C under reduced pressure for 1 hour while stirring.
[0083] Thereafter, the pressure was returned to normal pressure with nitrogen, 19.5 parts by mass of diphenylmethane diisocyanate was added, the internal temperature was raised to 110° C., and the reaction was carried out for 1 hour under a nitrogen stream.
[0084] Thereafter, the mixture was further degassed under reduced pressure at 110° C. for 1 hour to obtain an adhesive composition.
[0085] [Example 2] An adhesive composition was obtained in the same manner as in Example 1, except that the (meth)acrylic polymer (a) was replaced with the (meth)acrylic polymer (b).
[0086] [Example 3] An adhesive composition was obtained in the same manner as in Example 1, except that the filler (b) was used instead of the filler (a).
[0087] [Comparative Example 1] A composition was obtained in the same manner as in Example 1, except that no filler was used.
[0088] [Comparative Example 2] A composition was obtained in the same manner as in Example 1, except that no (meth)acrylic polymer was used.
[0089] [Comparative Example 3] A composition was obtained in the same manner as in Example 1, except that the (meth)acrylic polymer (a) was replaced with the (meth)acrylic polymer (c).
[0090] [Comparative Example 4] A composition was obtained in the same manner as in Example 1, except that the (meth)acrylic polymer (a) was replaced with the (meth)acrylic polymer (d).
[0091] [Table 1]
[0092] [Evaluation Results] The adhesive compositions obtained in Examples 1 to 3 all had high initial adhesive strength and low melt viscosity.
[0093] The composition obtained in Comparative Example 1 did not contain a filler (C) and had a low initial adhesive strength. The composition obtained in Comparative Example 2 did not contain a (meth)acrylic polymer (B) and had a low initial adhesive strength. The composition obtained in Comparative Example 3 contained a (meth)acrylic polymer with a high molecular weight and a high melt viscosity. The composition obtained in Comparative Example 4 contained a (meth)acrylic polymer with a low glass transition temperature and had a low initial adhesive strength.
[0094] From the above, it can be seen that a reactive hot melt adhesive composition containing a urethane prepolymer (A) consisting of a structure derived from a polyol and a compound having an isocyanate group at at least one end of the polyol-derived structure, a (meth)acrylic polymer (B) which is a polymer having a structural unit derived from a (meth)acrylic acid ester, and a filler (C), wherein the (meth)acrylic polymer (B) has a glass transition temperature of 65°C or higher and the (meth)acrylic polymer (B) has a weight average molecular weight of 100,000 or less, has high initial adhesive strength and low melt viscosity.
Claims
1. A reactive hot melt adhesive composition comprising: a urethane prepolymer (A) consisting of a compound having a structure derived from a polyol and an isocyanate group at at least one end of the structure derived from the polyol; a (meth)acrylic polymer (B) which is a polymer having a structural unit derived from a (meth)acrylic acid ester; and a filler (C), wherein the (meth)acrylic polymer (B) has a glass transition temperature of 65° C. or higher and a weight average molecular weight of 100,000 or less.
2. 10. The reactive hot melt adhesive composition of claim 1 further comprising a thermoplastic elastomer.
3. The reactive hot melt adhesive composition according to claim 1 or 2, wherein the filler (C) comprises an inorganic filler.
4. 3. The reactive hot melt adhesive composition according to claim 1, wherein the (meth)acrylic polymer (B) has a glass transition temperature of 100° C. or lower.
5. The reactive hot melt adhesive composition according to claim 1 or 2, wherein the structure derived from the polyol includes at least one of a structure derived from a polyester polyol and a structure derived from a polyether polyol.
6. The reactive hot melt adhesive composition according to claim 1 or 2, wherein the urethane prepolymer (A) comprises a polyester polyol having an isocyanate group at least at either end and a polyether polyol having an isocyanate group at least at either end.
7. 3. The reactive hot melt adhesive composition according to claim 1, wherein the content of the urethane prepolymer (A) is 45% by mass or more and 95% by mass or less, the content of the (meth)acrylic polymer (B) is 3.0% by mass or more and 25% by mass or less, and the content of the filler (C) is 1.0% by mass or more and 10% by mass or less.
8. 3. The reactive hot melt adhesive composition according to claim 2, wherein the content of the urethane prepolymer (A) is 45% by mass or more and 90% by mass or less, the content of the (meth)acrylic polymer (B) is 3.0% by mass or more and 25% by mass or less, the content of the filler (C) is 1.0% by mass or more and 10% by mass or less, and the content of the thermoplastic elastomer is 3.0% by mass or more and 20% by mass or less.
9. 3. The reactive hot melt adhesive composition according to claim 1, wherein the initial adhesive strength, which is the adhesive strength one minute after adhesion, is 0.17 MPa or more and the melt viscosity at 120°C is 9.0 Pa·s or less.
10. applying a molten reactive hot melt adhesive composition to a first member; a mounting step of mounting a second member on the surface of the first member on which the reactive hot melt adhesive composition is applied; A reaction step of reacting the applied reactive hot melt adhesive composition in moisture-containing air, The reactive hot melt adhesive composition comprises a urethane prepolymer (A) consisting of a compound having a structure derived from a polyol and an isocyanate group at at least one end of the structure derived from the polyol, a (meth)acrylic polymer (B) which is a polymer having a structural unit derived from a (meth)acrylic acid ester, and a filler (C), wherein the (meth)acrylic polymer (B) has a glass transition temperature of 65°C or higher and a weight average molecular weight of 100,000 or less.
Citation Information
Patent Citations
Reactive hottmelt adhesive
JP1977037936A
Thermally stable reactive hot melt urethane adhesive composition containing thermoplastic polymer, cured urethane polyalkylene polyol prepolymer having adaptability and sticking imparting agent
JP1989054089A
Reactive hot melt adhesive composition
JP1994122860A
Moisture-curable reactive hot-melt adhesive composition
JP2019172881A
Reactive hot melt adhesive composition
JP6662376B2